PENGARUH PEMBERIAN TOPIKAL EKSTRAK KOLAGEN KULIT IKAN LELE SANGKURIANG (CLARIAS GARIEPINUS VAR) TERHADAP TNF-Î‘ DAN JUMLAH FIBROBLAST PADA LUKA BAKAR DERAJAT DUA TIKUS WISTAR - ., Aisyah; Mufarikoh, Zainatul; Andini, Ary (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
ABSTRACTBackground: Collagen has vital role on healing process of burn injuries, mainly in connective tissue.Collagen triggers fibroblast proliferation, support to form new granulation tissue and epithelium aroundwound. Wound treatment through collagen extract of Sangkuriang catfish skin can increase healing process.It stimulates humidity on level II burn injuries and encourage re-epithelization, proliferation and cellmigration also increases growth. Methods: This is an experimental studies using 4 groups of RattusNorvegicus (Wistar strain). All of the group get a burn injuries in their back skin. Control group 1 (K1) wastreated by lidocaine for three days and control group 2 (K2) for ten days. Whereas treatment group 1 (P1) getlidocaine and collagen extract from Sangkuriang cat fish for 3 days and treatment group 2 (P2) for 10 days.Result: Number of fibroblast/field of view on treatment group showed significantly increased comparedcontrol groups on the 3rd days (P=0,046) and the 10th (P=0,004). Percentage of TNF-? on level II-burninjuries in wistar rats showed significant difference. Percentage of TNF-? lower than treatment group andshowed significant lowering level compared control groups on the10th (P=0,022). Conclusion: Increasing offiroblast number and lowering level of TNF-? significantly showed collagen extract of Sangkuriang cat fishskin accelerate wound healing process.